DEVELOPMENT OF A PROJECT TO IMPROVE THE COMPANY'S PERSONNEL MANAGEMENT SYSTEM (Academicia Globe: Inderscience Research, 2024)
This article outlines a comprehensive approach to developing a project aimed at enhancing the personnel management system within a company. Beginning with a needs assessment and stakeholder engagement, the project progresses through stages such as defining objectives, selecting appropriate tools/systems, customization, implementation, data migration, testing, rollout, and ongoing monitoring and evaluation. Emphasizing continuous improvement, the article offers practical guidance on each step of the process, highlighting the importance of aligning the project with the organization's strategic goals and fostering stakeholder buy-in. By following the outlined plan, companies can effectively address existing challenges, streamline processes, and improve overall efficiency in managing personnel, thereby contributing to enhanced employee satisfaction and organizational performance.